Correction: Synthesis of hydrophobic and hydrophilic TiO2 nanofluids for transformable surface wettability and photoactive coating. Issue 77 (12th September 2019) - Hu, Jie; Zhao, Tian; Geng, Wei; Lu, Yi; Zhao, Xiao-Fang; Li, Yuan-Zhou; Tang, Yu-Qian; Liu, Jia-Wen; Wang, Li-Ying; Janiak, Christoph; Yang, Xiao-Yu; Su, Bao-Lian
Abstract : Correction for 'Synthesis of hydrophobic and hydrophilic TiO2 nanofluids for transformable surface wettability and photoactive coating' by Jie Hu et al., Chem. Commun., 2019, 55, 9275–9278.